In sickness and in health: the dynamics of the fruit bat gut microbiota under a bacterial antigen challenge and its association with the immune response - Berman, Tali S.; Weinberg, Maya; Moreno, Kelsey R.; Czirják, Gábor Á.; Yovel, Yossi (Frontiers in Immunology, 2023)
Interactions between the gut microbiome (GM) and the immune system influence host health and fitness. However, few studies have investigated this link and GM dynamics during disease in wild species. Bats (Mammalia: Chiroptera) have an exceptional ability to cope with intracellular pathogens and a unique GM adapted to powered flight. Yet, the contribution of the GM to bat health, especially immunity, or how it is affected by disease, remain unknown. Here, we examined the dynamics of the Egyptian fruit bats’ (Rousettus aegyptiacus) GM during health and disease. We provoked an inflammatory response in bats using lipopolysaccharides (LPS), an endotoxin of Gram-negative bacteria. We then measured the inflammatory marker haptoglobin, a major acute phase protein in bats, and analyzed the GM (anal swabs) of control and challenged bats using high-throughput 16S rRNA sequencing, before the challenge, 24h and 48h post challenge. We revealed that the antigen challenge causes a shift in the composition of the bat GM (e.g., Weissella, Escherichia, Streptococcus). This shift was significantly correlated with haptoglobin concertation, but more strongly with time. Eleven bacterial sequences were correlated with haptoglobin concentration and nine were found to be potential predictors of the strength of the immune response, and implicit of infection severity, notably Weissella and Escherichia. The bat GM showed high resilience, becoming similar to that of control bats within 48h of the challenge, as bats resumed foraging and social activities. Our results demonstrate a tight link between bat immune response and changes in their GM, and emphasize the importance of integrating microbial ecology in ecoimmunological studies of wild species. The resilience of the GM may provide this species with an adaptive advantage to cope with infections and maintain colony health.